Geoeffectiveness of interplanetary shocks controlled by impact angles: past research, recent advancements, and future work - Oliveira, Denny M. (Frontiers in Astronomy and Space Sciences, 2023)
Interplanetary (IP) shocks are disturbances commonly observed in the solar wind. IP shock impacts can cause a myriad of space weather effects in the Earth's magnetopause, inner magnetosphere, ionosphere, thermosphere, and ground magnetic field. The shock impact angle, measured as the angle the shock normal vector performs with the Sun-Earth line, has been shown to be a very important parameter that controls shock geoeffectivess. An extensive review provided by Oliveira and Samsonov (2018) summarized all the work known at the time with respect to shock impact angles and geomagnetic activity; however, this topic has had some progress since Oliveira and Samsonov (2018) and the main goal of this mini review is to summarize all achievements to date in the topic to the knowledge of the author. Finally, this mini review also brings a few suggestions and ideas for future research in the area of IP shock impact angle geoeffectiveness.